The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s40364-020-00233-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tRNA-derived fragments and tRNA halves in cancer treatment resistance

Abstract: The tRNA-derived fragments (tRFs) and tRNA halves (tiRNAs) are newly discovered noncoding RNAs in recent years. They are derived from specific cleavage of mature and pre-tRNAs and expressed in various cancers. They enhance cell proliferation and metastasis or inhibit cancer progression. Many studies have investigated their roles in the diagnosis, progression, metastasis, and prognosis of various cancers, but the mechanisms through which they are involved in resistance to cancer treatment are unclear. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 165 publications
0
29
0
2
Order By: Relevance
“…Additionally, there are literally hundreds of studies purporting that dysregulation of tRFs is related to cancers of various types [ 108 , 109 , 110 ]; however, the underlying mechanisms remain largely unknown, both in terms of what alters tRNA processing and what signaling cascades are triggered by tRF dysregulation [ 20 ]. In addition to their potential utility as biomarkers, tRF levels might also indicate how well cells will respond to various kinds of therapy, though again mechanistic explanations remain poorly understood [ 103 , 111 ].…”
Section: Diversification Of Ncrna Functionmentioning
confidence: 99%
“…Additionally, there are literally hundreds of studies purporting that dysregulation of tRFs is related to cancers of various types [ 108 , 109 , 110 ]; however, the underlying mechanisms remain largely unknown, both in terms of what alters tRNA processing and what signaling cascades are triggered by tRF dysregulation [ 20 ]. In addition to their potential utility as biomarkers, tRF levels might also indicate how well cells will respond to various kinds of therapy, though again mechanistic explanations remain poorly understood [ 103 , 111 ].…”
Section: Diversification Of Ncrna Functionmentioning
confidence: 99%
“…Further analyses revealed that the two elevated tDRs are involved in the maintenance of stem cell numbers and interleukin (IL)‐6 responses [ 128 ]. IL-6 is involved in multidrug resistance by activating JAK/STAT3, PI3K/Akt, and other pathways [ 129 ]. Moreover, protein–protein interaction (PPI) analysis showed that tDR-0009/tDR-7336 is closely associated with the STAT3 protein [ 128 ].…”
Section: Roles In Diseasementioning
confidence: 99%
“…Drug resistance is considered a vital factor determining the efficacy of anti-cancer therapies. Emerging evidence showed that some tsRNAs modulated the drug resistance of multiple tumours ( 24 ). For example, Cui et al.…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%